2022
DOI: 10.1177/17562848221142417
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of sarcopenia in patients with hepatocellular carcinoma treated with PD-1 inhibitor

Abstract: Background: Sarcopenia is a progressive generalized loss of skeletal muscle mass commonly observed in advanced stages of cancer. Objective: To assess the relationship between sarcopenia and the prognosis of patients with hepatocellular carcinoma (HCC) treated with a programmed cell death 1 (PD-1) inhibitor. Design: This is a retrospective study. Methods: This study included patients with HCC treated with camrelizumab between 1 March 2020 and 1 December 2021. The skeletal muscle area at the L3 vertebra middle l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The meta-analysis included 20 retrospective studies involving a total of 2377 patients with HCC who received systemic therapy [11,12,[14][15][16][17][19][20][21][22][23][24][25][26][31][32][33][34][35][36]. One study reported the prevalence of LSMM and survival analysis results separately for lenvatinib and immunotherapy [20], while another conducted survival analysis separately for males and females [16].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis included 20 retrospective studies involving a total of 2377 patients with HCC who received systemic therapy [11,12,[14][15][16][17][19][20][21][22][23][24][25][26][31][32][33][34][35][36]. One study reported the prevalence of LSMM and survival analysis results separately for lenvatinib and immunotherapy [20], while another conducted survival analysis separately for males and females [16].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Earlier studies investigated the effect of LSMM on survival in patients undergoing HCC treatment. Among patients receiving immunotherapy [11,[19][20][21][22][23], most studies report no significant association between LSMM and survival [20,24,25], with the exception of two studies [19,26]. Therefore, an updated review and meta-analysis of this topic is needed to gain a better understanding of the relationship between LSMM and the outcomes of HCC patient undergoing a variety of systemic therapy regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the correlation between immunotherapy or immune-targeted combination therapy and sarcopenia, multiple studies have presented varying perspectives. [29][30][31][32] Kuo et al 19 conducted a meta-analysis on the 184 aforementioned studies, ultimately indicating the widespread presence of low skeletal muscle mass in HCC patients undergoing different systemic treatment types, significantly correlating with adverse prognosis. Compared to our study, despite differences in the cut-off values used in various studies, the majority utilized L3-SMI to assess muscle mass, consistent with our research methodology.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in camrelizumab-treated patients, sarcopenia was related to lower PFS but not to a lower OS, even if a trend toward lower OS in sarcopenic individuals was observed [125]. The presence of sarcopenia was related to higher inflammatory markers and lower levels of albumin, another marker of both malnutrition and reduced liver function [125].…”
Section: Impact Of Sarcopenia On Systemic Treatment Outcomesmentioning
confidence: 97%
“…A European study conducted on patients treated with various anti-PDL1 regimens confirmed that sarcopenia negatively affected OS, especially in patients with higher systemic inflammation activation [124]. On the other hand, in camrelizumab-treated patients, sarcopenia was related to lower PFS but not to a lower OS, even if a trend toward lower OS in sarcopenic individuals was observed [125]. The presence of sarcopenia was related to higher inflammatory markers and lower levels of albumin, another marker of both malnutrition and reduced liver function [125].…”
Section: Impact Of Sarcopenia On Systemic Treatment Outcomesmentioning
confidence: 98%